Malaysian Special Economic Zone: Analysing the Land Use Planning Through Development Plan - Najimudin, Muhammad Fadhlullah; Md Dahlan, Nuarrual Hilal; Md. Nor, Mohd Zakhiri (2021)
Policymakers often use Special Economic Zones (SEZs) as a strategy to boost micro and macroeconomist. Its successful global implementation can still be questioned with frequent development operational problems, specifically from the legal perspective. Therefore, this paper explores the loopholes in the development plan implementation in exercising land use planning for SEZs' development in Malaysia. Two significant legal issues in implementing the development plan and land use planning control based on the statutory provision and legal cases have been identified using qualitative textual analysis. Findings show a lack of empowerment of statutory development plans and local authorities' decisions on land use planning management-related matters. Therefore, further understanding of the land use planning implementation's legal issues is vital in formulating SEZs development's regulatory framework in Malaysia.